A PMG Approach to the Joint Effects of Oil Price Changes and Environmental Risks on Non-Performing Loans: Evidence from Organisation of the Petroleum Exporting the Countries - Idris, Ismail Tijjani; Nayan, Sabri (International Journal of Energy Economics and Policy, 2017)
This paper revisits the work of Idris and Nayan (2016a) on the joint effects of oil price volatility and environmental risks on Non-performing loans (NPLs). Therefore, the current paper uses evidence from 13 Organisation of the Petroleum Exporting countries spanning 1996-2015. The present situation of worldwide NPLs is persistent and on the rise which indicates a global deterioration of loans qualities. The NPLs is more pronounced amongst the OPEC countries whose average ratio of NPLs is on the verge of the banking crisis. This directly affects further loan creation, banks’ liquidity, investment and productivity. Notwithstanding, the different measures put in place by regulatory authorities in OPEC countries to tackle the situation, the problem persists. The motivation of this paper is to examine the impact of systematic risks factors of oil price changes and environmental risks on NPLs by employing Pooled Mean Group (PMG) methods. The results reveal that oil price changes significantly but inversely affect NPLs while environmental risks factor is found to be significantly and positively affecting NPLs. The policy implications of the findings are that for the OPEC countries to achieve financial stability they should reduce the impact of systematic risks on their financial systems. Therefore, for a continuous minimization of bad loans, the OPEC economies should efficiently increase their earnings from the oil exportation or alternatively through increased diversification of the OPEC economies from the monoculture economic activity of oil exportation. Furthermore, environmental risks should be mitigated through strong legislation for all businesses and economic units in the countries to be covered by adequate insurance covers against these calamities. Finally, OPEC governments should ensure that their prudential guidelines cover lending to business activities that are prone to such systematic risks. Keywords: Non-performing loans, oil price, environmental risks, OPEC countries, pooled mean group methods JEL Classification: G32, Q43, Q54